Prospecção fitoquímica e atividade antioxidante da espécie Goupia glabra (Cupiúba) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
It is estimated that in Brazil more than 25 million tons of wood residues are generated every year. The main generating source is the wood industry, cooperating with 90% of the residues from wood. In this context, the work aimed to carry out phytochemical prospecting and evaluation of antioxidant activity against the DPPH and ABTS radicals of the Goupia glabra (cupiúba) extract of the Celastraceae family. For this, the ethanolic extract was prepared from wood residues for the qualitative evaluation of some secondary metabolites (phenols, flavonoids and condensed tannins), quantitative of phenolic and flavonoids and evaluation of the antioxidant capacity in vitro (DPPH and ABTS). The analytical protocols used were carried out by spectrophotometric tests. The results showed that the extract of the evaluated residue presented compounds of the class of phenolics and flavonoids, significant quantitative content of phenolics and flavonoids, in addition to antioxidant activity against DPPH and ABTS radicals. The results obtained with the extract of the cupiúba residue proved to be promising, presenting potential to be used as an input in the pharmaceutical, food and cosmetic industry.
Keywords: Resíduo; Goupiaceae; Antioxidante; CNPQ:: CIÊNCIAS DA SAÚDE